Pengaruh Konseling Obat Terhadap Pengetahuan dan Kepatuhan Pasien Congestive Heart Failure - Elfia Neswita; Dedy Almasdy; Harisman Harisman (Fakultas Farmasi Universitas Andalas, 2016)
Compliance therapy is a very important point in the successful treatment of CHF patients. However, such compliance is very low so do efforts to increase knowledge and treatment adherence through drug counseling by pharmacists. The design of this type of research is a quasi-experimental, one-group pretest-posttest design, with a population of CHF patients in IRNA Heart Hospital DR. M. Djamil Padang in the month from March to December 2014. The sampling technique in the form of purposive sampling (50 patients) with questionnaires and interviews. Data analysis was performed using the Crosstab, Chi-Square, paired-sample t-test, Pearson Product Moment, simple linear regression, multiple linear regression and SPSS version 17. The results of this study indicate that the drug counseling significantly improve patient knowledge and compliance (97,2% and 77.6% (p <0.05)).